Education as a Prerequisite for Social Exclusion/Inclusion - Pirimova, Elka (Research Papers, 2025)
The article analyzes certain aspects of the problem of poverty and social exclusion/resp. inclusion in Bulgaria. More specifically, the trends in the dynamics of unemployment and employment according to the level of education and the age of the workforce were examined. The author applies the methods of analysis and synthesis, methods of comparative and descriptive analysis. The results show that a limited and partial manifestation of positive trends was achieved during the period 2013 – 2023, which are insufficient to overcome the problem and improve Bulgaria's position within the EU.
Keywords: Employment; Unemployment; Poverty and social exclusion/inclusion